2016
DOI: 10.1021/acscatal.6b01681
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of Di- and Tri-Arylated All-Carbon Quaternary Stereocenters via Copper-Catalyzed Allylic Arylations with Organolithium Compounds

Abstract: All reactions were carried out under nitrogen atmosphere in oven-dried glassware using standard Schlenk techniques. All allylic substitution reactions were performed in an ethanol bath cooled to -80 °C using a cryostat. Dichloromethane, diethyl ether, tetrahydrofuran and toluene were dried via a solvent purification system (MBRAUN SPS systems, MB-SPS-800).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 86 publications
0
14
0
Order By: Relevance
“…37, 38 Feringa later showed that aryllithium reagents can be deployed directly in copper-catalyzed allylic substitutions of allyl bromides using triazolium-derived NHC ligand XIII , although incomplete regioselectivity was observed. 39 More recently, Hoveyda 40 and Hayashi 41, 42 applied more tractable organoboronates to the asymmetric vinylation and arylation of γ,γ-disubstituted allylic phosphates under non-cryogenic conditions. Finally, Sawamura and Ohmiya showed that azoles bearing acidic C-H bonds are subject to direct deprotonation-allylic substitution under the conditions of copper catalysis.…”
Section: Acyclic Quaternary Carbon Stereocentersmentioning
confidence: 99%
“…37, 38 Feringa later showed that aryllithium reagents can be deployed directly in copper-catalyzed allylic substitutions of allyl bromides using triazolium-derived NHC ligand XIII , although incomplete regioselectivity was observed. 39 More recently, Hoveyda 40 and Hayashi 41, 42 applied more tractable organoboronates to the asymmetric vinylation and arylation of γ,γ-disubstituted allylic phosphates under non-cryogenic conditions. Finally, Sawamura and Ohmiya showed that azoles bearing acidic C-H bonds are subject to direct deprotonation-allylic substitution under the conditions of copper catalysis.…”
Section: Acyclic Quaternary Carbon Stereocentersmentioning
confidence: 99%
“…Mostly known as convenient, air-stable precursors to N -heterocyclic carbenes (NHCs) used in organocatalytic transformations, 1,2,4-triazolium salts also form upon deprotonation of NHC ligands for transition metal catalysts. Beyond the field of catalysis, these 1,2,4-triazole-based ligands form phosphorescent cyclometalated complexes with the substituents on the carbene ligand being key to their tunable emission wavelengths, while other late transition metal complexes containing 1,2,4-triazole ligands have shown promising in vitro anticancer activity in studies involving breast, colon, lung, skin, liver, and cervical cancer as well as leukemia. N -Aryl-substituted 1,2,4-triazoles are also frequent building blocks in organic compounds with biological activity. Although less common than imidazolium or 1,2,3-triazolium salts, 1,2,4-triazolium salts have been successfully used as ionic liquids for dissolving cellulose …”
Section: Introductionmentioning
confidence: 99%
“…Pd-catalyzed asymmetric allylic substitution reactions of vinyl epoxides 7 and vinyl cyclic carbonates (VCCs) 8 serving as prochiral electrophilic allylic surrogates have been recently reported as efficient approaches to forge compounds featuring a tetrasubstituted carbon stereocenter. While only a handful of studies report the efficient use of olefin-substituted VCCs in allylic alkylation (Scheme 1b, R 2 -R 4 ≠ H) 9 and more particularly towards branched allylic products, 9h,i as far as we are aware only two reports exist that briefly discuss the use of more elaborate carbonate ring substituted congeners (Scheme 1b, R 5 and R 6 ≠ H). 9f,g The successful conversion of these latter types of congested substrates in transformations leading to compounds having vicinal tetrasubstituted carbon centers would greatly expand the application potential of VCCs and advance the synthesis of otherwise elusive carbon stereocenters.…”
mentioning
confidence: 99%